GAMBARAN PENGETAHUAN MASYARAKAT TERHADAP PERMEN JELLY BUAH KUPA (Syzygium polycephalum) SEBAGAI ANTIOKSIDAN DI DESA SIDOLUHUR - Dharmayanti, Luky; Aufa, Dzakiyah; Adinda Frisca (Fakultas Pertanian, 2024)
The gowok plant (Syzygium polycephalum) is still a member of the guava tribe (Myrtaceae) which is also one of the endemic plants in Indonesia. Kupa fruit has red to purple skin. Anthocyanin is a content contained in kupa fruit skin. Pigments belonging to the flavonoid class which play a role in producing the red, blue and purple colors in many flowers and fruit are called anthocyanins. Therefore, anthocyanins have potential as natural dyes and as antioxidants. The aim of this research is to educate the people of Sidoluhur Village about the properties, formulation and method of making kupa fruit jelly candy. The method used in this counseling is the group method by educating and asking questions through questionnaires and group discussions. The results obtained based on the pre-test were as follows: 73% of the audience did not know about kupa fruit, 93% of the audience did not know about the properties of kupa fruit, 100% of the audience did not know the benefits of kupa fruit as an antioxidant and did not know how to make jelly candy. The results of the herdonic test for Kupa fruit jelly candy are as follows: 87% of the audience likes the texture of Kupa jelly candy, 83% of the audience likes the taste of Kupa jelly candy, 90% of the audience likes the aroma of Kupa jelly candy, and 100% of the audience likes the color of Kupa jelly candy. From the results of the questionnaire before the counseling, there were still many audiences who did not know about kupa fruit and the benefits of kupa fruit, and the entire audience did not know and had never made kupa jelly candy. In the hedonic test or taste test, the audience liked the formulation that we made for the texture, taste, aroma and color of the kupa jelly candy.